Genomic characterization of coagulase-negative staphylococci including methicillin-resistant Staphylococcus sciuri causing bovine mastitis - Khazandi, M.; Al-Farha, A.; Coombs, Geoffrey; O'Dea, M.; Pang, S.; Trott, D.; Aviles, R.; Hemmatzadeh, F.; Venter, H.; Ogunniyi, A.; Hoare, A.; Abraham, S.; et al. (Elsevier, 2018)
Methicillin-resistant coagulase-negative staphylococci (MRCoNS) have recently emerged as a significant cause of bovine mastitis worldwide. Here we describe the isolation of MRCoNS from cases of bovine mastitis from a single dairy farm in Australia. Fourteen CoNS isolates were identified as MRCoNS on the basis of having an oxacillin MIC of =0.5 µg/mL. The isolates were speciated as S. chromogenes (n = 1) S. fleurettii (n = 1), S. haemolyticus (n = 2), S. sciuri (n = 5), S. simulans (n = 1) S. succinus (n = 2) and S. xylosus (n = 2). Five of the isolates (S. fleuretti, S. haemolyticus S. sciuri and two S. succinus) were mecA-positive. We also detected a previously described S. sciuri mecA homolog in four oxacillin-resistant S. sciuri isolates. The remainder of the putative MRCoNS did not contain any mecA-related resistance determinants in their genomes. Comparative genomic analysis of three previously published S. sciuri isolates, from humans, a squirrel and a cereal crop (rice), and a representative isolate from our study demonstrated clustering and a high degree of genetic homogeneity (>95%), suggesting S. sciuri has low host specificity. In conclusion, CoNS, in particular S. sciuri, may act as a reservoir for SCCmec elements that can easily be spread between different host species by direct cross-infection.